The influence of fibroblast growth factor 2 on the senescence of human adipose‐derived mesenchymal stem cells during long‐term culture. (16th December 2019) - Cheng, Yin; Lin, Kai‐Hsuan; Young, Tai‐Horng; Cheng, Nai‐Chen
Abstract: Adipose‐derived mesenchymal stem cells (ASCs) exhibit great potential in regenerative medicine, and in vitro expansion is frequently necessary to obtain a sufficient number of ASCs for clinical use. Fibroblast growth factor 2 (FGF2) is a common supplement in the ASC culture medium to enhance cell proliferation. To achieve clinical applicability of ASC‐based products, prolonged culture of ASCs is sometimes required to obtain sufficient quantity of ASCs. However, the effect of FGF2 on ASCs during prolonged culture has not been previously determined. In this study, ASCs were subjected to prolonged in vitro culture with or without FGF2. FGF2 maintained the small cell morphology and expedited proliferation kinetics in early ASC passages. After prolonged in vitro expansion, FGF2‐treated ASCs exhibited increased cell size, arrested cell proliferation, and increased cellular senescence relative to the control ASCs. We observed an upregulation of FGFR1c and enhanced expression of downstream STAT3 in the initial passages of FGF2‐treated ASCs. The application of an FGFR1 or STAT3 inhibitor effectively blocked the enhanced proliferation of ASCs induced by FGF2 treatment. FGFR1c upregulation and enhanced STAT3 expression were lost in the later passages of FGF2‐treated ASCs, suggesting that the continuous stimulation of FGF2 becomes ineffective because of the refractory downstream FGFR1 and the STAT3 signaling pathway. In addition, no evidence of tumorigenicity was noted in vitro and in vivo after prolonged expansion of FGF2‐cultured ASCs. Our data indicate that ASCs have evolved a STAT3‐dependent response to continuous FGF2 stimulation which promotes the initial expansion but limits their long‐term proliferation. Abstract : Fibroblast growth factor 2 (FGF2) exerts positive effects in the early passages of adipose‐derived mesenchymal stem cells (ASCs), including maintenance of cellular morphology, less senescent cells, and expedition of proliferative kinetics. However, after prolonged in vitro expansion with FGF2, decreased proliferation with more senescent cells was noted, which was probably mediated through FGFR1 and the downstream STAT3 signaling pathway.